An organic compound and its application and an organic electroluminescent device using the same

By using B-N organic photoelectric materials with dual B atomic structure in organic electroluminescent devices, the problems of roll-off efficiency and short life of existing materials at high brightness are solved, and higher fluorescence quantum yield and stability are achieved.

CN112940023BActive Publication Date: 2025-02-21BEIJING DINGCAI TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN201911262793.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-12-11
Publication Date
2025-02-21
Estimated Expiration
2039-12-11

AI Technical Summary

Technical Problem

The existing organic electroluminescent materials have severe annihilation at high brightness, resulting in severe rollover of efficiency and short device life, limiting their further development in the field of display and lighting.

Method used

Provided a B-N organic photoelectric material with a bi-B atomic structure, used as a luminescent layer material in an organic electroluminescent device, and improves fluorescence quantum yield and device stability through its rigid planar conjugated structure and rehydrogenation of partial atoms. sex.

Benefits of technology

It improves the fluorescence quantum yield and stability of organic electroluminescent devices, reduces driving voltage and improves device life, and significantly improves luminous performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112940023B_ABST
    Figure CN112940023B_ABST
Patent Text Reader

Abstract

The present invention relates to a novel organic compound having the following structure: a , R b , R c , R d and R e Each independently represents a single substituent to the maximum permissible substituent, and each independently is selected from hydrogen, substituted or unsubstituted C1-C12 chain alkyl, substituted or unsubstituted C3-C12 cycloalkyl, substituted or unsubstituted C1-C12 alkoxy, halogen, cyano, nitro, hydroxyl, silane, amino, substituted or unsubstituted C6-C30 arylamino, substituted or unsubstituted C3-C30 heteroarylamino, substituted or unsubstituted C6-C30 aryl, substituted or unsubstituted C3-C30 heteroaryl, at least one hydrogen in the compound structure represented by formula (1) is deuterated. When the compound of the present invention is used as a light-emitting layer material in an OLED device, it exhibits excellent device performance and stability. The present invention also protects an organic electroluminescent device using the compound of the above general formula.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a novel organic compound, in particular to a compound which can be used in an organic electronic device. The present invention also relates to an organic electroluminescent device using the compound. Background Art

[0002] At present, optoelectronic devices using organic materials are becoming more and more popular. Many materials used to manufacture such devices are relatively cheap, and optoelectronic devices have potential cost advantages compared to inorganic devices. In the current organic electroluminescent device structure in the display and lighting field, blue fluorescence is generally used in combination with red and green phosphorescent materials. Recently, a literature has reported an ultra-pure blue fluorescent compound DABNA-1 and DABNA-2 based on the BN resonance structure of TADF (Thermally Activated Delayed Fluorescence). This type of compound consists of a rigid polycyclic aromatic skeleton composed of B, N and benzene rings. The nitrogen atom has a resonance effect opposite to that of the boron atom, and the opposite resonance effect is enhanced at its para position. Therefore, this effect can clearly separate the HOMO and LUMO orbitals, and thus has certain TADF characteristics.

[0003]

[0004] Although this series of materials has good color purity, the reverse intersystem hopping rate is low, and the triplet-triplet annihilation under high brightness is relatively serious, which leads to severe efficiency roll-off and short device life, seriously restricting its further development.

[0005] Existing organic electroluminescent materials still have much room for improvement in luminescence performance, and the industry urgently needs to develop new luminescent material systems to meet commercial needs. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a novel compound, specifically a BN organic photoelectric material with a double B atom structure, and also provides the application of the compound in an organic electroluminescent device.

[0007] The novel compound of the present invention has a structure represented by the general formula (1):

[0008]

[0009] In formula (1), the dotted line indicates that they can be connected to form a ring or not;

[0010] R a , R b , R c , Rd and R e Each independently represents a single substituent to the maximum permissible substituent, and is independently selected from one of hydrogen, substituted or unsubstituted C1-C12 chain alkyl, substituted or unsubstituted C3-C12 cycloalkyl, substituted or unsubstituted C1-C12 alkoxy, halogen, cyano, nitro, hydroxyl, silane, amino, substituted or unsubstituted C6-C30 arylamino, substituted or unsubstituted C3-C30 heteroarylamino, substituted or unsubstituted C6-C30 aryl, and substituted or unsubstituted C3-C30 heteroaryl;

[0011] Ar 1 and Ar 2 Each is independently selected from a substituted or unsubstituted C6-C30 aryl group, a substituted or unsubstituted C3-C30 heteroaryl group;

[0012] Ar 1 With Ring 1 and / or R a Connected into a ring or not connected into a ring;

[0013] Ar 1 With Ring 2 and / or R e Connected into a ring or not connected into a ring;

[0014] Ar 2 With Ring 2 and / or R e Connected into a ring or not connected into a ring;

[0015] Ar 2 With Ring 3 and / or R d Connected into a ring or not connected into a ring;

[0016] Furthermore, at least one hydrogen in the compound structure represented by formula (1) is deuterated;

[0017] When the above-mentioned substituted or unsubstituted groups have substituents, the substituents are selected from one or more of deuterium, halogen, C1-C12 chain alkyl, C3-C12 cycloalkyl, deuterated C1-C12 chain alkyl, deuterated C3-C12 cycloalkyl, C1-C12 alkoxy or thioalkoxy, C6-C30 arylamino, C3-C30 heteroarylamino, C6-C30 monocyclic aromatic or condensed aromatic, C3-C30 monocyclic heteroaryl or condensed heteroaryl.

[0018] More preferably, in the above formula (1), R a , R b , R c , R d and R e One hydrogen in at least one of the ring structures is deuterated.

[0019] More preferably, in the above formula (1), R a , R b , R c , R d and R e At least one of them is a deuterated C1-C12 chain alkyl group or a deuterated C3-C12 cycloalkyl group.

[0020] More preferably, in the above formula (1), Ar 1 and Ar 2 Each is independently selected from a substituted C6-C30 aryl group having at least one substituent group, or a substituted C3-C30 heteroaryl group having at least one substituent group, wherein the substituent group is selected from deuterium, a deuterated C1-C12 chain alkyl group or a deuterated C3-C12 cycloalkyl group.

[0021] Still more preferably, the compound of the present invention has the structural formula (2):

[0022]

[0023] In formula (2), the dotted line indicates that they can be connected to form a ring or not;

[0024] R a , R b , R c , R d and R e The definition of is the same as that in formula (1);

[0025] R f and R g Each independently represents a single substituent to the maximum permissible substituent, and is independently selected from one of hydrogen, substituted or unsubstituted C1-C12 chain alkyl, substituted or unsubstituted C3-C12 cycloalkyl, substituted or unsubstituted C1-C12 alkoxy, halogen, cyano, nitro, hydroxyl, silane, amino, substituted or unsubstituted C6-C30 arylamino, substituted or unsubstituted C3-C30 heteroarylamino, substituted or unsubstituted C6-C30 aryl, and substituted or unsubstituted C3-C30 heteroaryl;

[0026] When the above-mentioned substituted or unsubstituted groups have substituents, the substituents are selected from one or more of deuterium, halogen, C1-C12 chain alkyl, C3-C12 cycloalkyl, deuterated C1-C12 chain alkyl, deuterated C3-C12 cycloalkyl, C1-C12 alkoxy or thioalkoxy, C6-C30 arylamino, C3-C30 heteroarylamino, C6-C30 monocyclic aryl or condensed aryl, C3-C30 monocyclic heteroaryl or condensed heteroaryl;

[0027] Furthermore, at least one hydrogen atom in the compound structure represented by formula (2) is deuterated.

[0028] More preferably, in the above formula (2), R a , R b , R c , R d , R e and R f and R g At least one of them is deuterium.

[0029] More preferably, in the above formula (2), R a , R b , R c , R d , R e and R f and R g At least one of them is a deuterated C1-C12 chain alkyl group or a deuterated C3-C12 cycloalkyl group.

[0030] More preferably, the compounds of the present invention have the following structural formulas (2-1) to (2-6):

[0031]

[0032] In formula (2-1) to formula (2-6), R a , R b , R c , R d , R e , R f and R g The definition of is the same as that in formula (2), and at least one hydrogen in the compound structures represented by formula (2-1) to formula (2-6) is deuterated.

[0033] Further preferably, in the above formula (2-1) to formula (2-6), the R a , R b , R c , R d , R e and R f and R g At least one of them is deuterium.

[0034] Further preferably, in the above formula (2-1) to formula (2-6), the R a , R b , R c , R d , R e and R f and R gAt least one of them is a deuterated C1-C12 chain alkyl group or a deuterated C3-C12 cycloalkyl group.

[0035] More preferably, the compounds of the present invention have the following structural formulas (2-4) to (2-6):

[0036]

[0037] Further preferably, in the above formula (2-4) to formula (2-6), the R a , R b , R c , R d , R e and R f and R g At least one of them is deuterium.

[0038] Or further preferably, in the above formula (2-4) to formula (2-6), the R a , R b , R c , R d , R e and R f and R g At least one of them is a deuterated C1-C12 chain alkyl group or a deuterated C3-C12 cycloalkyl group.

[0039] It should be noted that, in the present invention, the maximum permissible substituent refers to the maximum number of substituents under the premise that the substituted group meets the requirements of the chemical bond. For example, the R a The number of can be one or more, but can only reach the maximum allowed substituents (i.e. 4).

[0040] In the present specification, the expression of Ca to Cb represents that the number of carbon atoms in the group is a to b. Unless otherwise specified, the number of carbon atoms generally does not include the number of carbon atoms in the substituent.

[0041] In the present specification, the expression of a ring structure crossed by “—” indicates that the connection site is any position on the ring structure that can form a bond.

[0042] In the present specification, the substituted or unsubstituted C6-C30 aryl group is preferably a C6-C20 aryl group, more preferably a phenyl group, a biphenyl group, a terphenyl group, a naphthyl group, an anthracenyl group, a phenanthrenyl group, an indenyl group, a fluorenyl group and its derivatives, a fluoranthenyl group, a triphenylene group, a pyrenyl group, a peryl group, A group consisting of a tetraphenyl group and a naphthyl group. Specifically, the biphenyl group is selected from 2-biphenyl, 3-biphenyl and 4-biphenyl; the terphenyl group includes p-terphenyl-4-yl, p-terphenyl-3-yl, p-terphenyl-2-yl, m-terphenyl-4-yl, m-terphenyl-3-yl and m-terphenyl-2-yl; the naphthyl group includes 1-naphthyl and 2-naphthyl; the anthracenyl group is selected from 1-anthracenyl, 2-anthracenyl and 9-anthracenyl; the fluorenyl group is selected from 1-fluorenyl, 2-fluorenyl, 3-fluorenyl, 4-fluorenyl and 9-fluorenyl; the fluorenyl derivative is selected from 9,9'-dimethylfluorene, 9,9'-spirobifluorene and benzofluorene; the pyrenyl group is selected from 1-pyrenyl, 2-pyrenyl and 4-pyrenyl; the tetraphenyl group is selected from 1-tetraphenyl, 2-tetraphenyl and 9-tetraphenyl.

[0043] The heteroatom in the present invention generally refers to an atom or an atom group selected from N, O, S, P, Si and Se, preferably selected from N, O and S.

[0044] In the present specification, the substituted or unsubstituted C3~C30 heteroaryl group is preferably a C4~C20 heteroaryl group, and more preferably a nitrogen-containing heteroaryl group, an oxygen-containing heteroaryl group, a sulfur-containing heteroaryl group, etc. Specific examples include: furyl, thienyl, pyrrolyl, benzofuranyl, benzothienyl, isobenzofuranyl, indolyl, dibenzofuranyl, dibenzothienyl, carbazole and derivatives thereof, wherein the carbazole derivative is preferably 9-phenylcarbazole, 9-naphthylcarbazole, benzocarbazole, dibenzocarbazole, or indolecarbazole.

[0045] In the present specification, the C1-C20 chain alkyl group is preferably a C1-C10 chain alkyl group, and more preferably a C1-C6 chain alkyl group, examples of which include methyl, ethyl, n-propyl, n-butyl, n-hexyl, n-octyl, isopropyl, isobutyl, and tert-butyl.

[0046] In the present specification, the C3-C12 cycloalkyl group includes a monocyclic alkyl group and a polycyclic alkyl group, and preferably a C1-C10 alkyl group and a C3-C10 cycloalkyl group.

[0047] Furthermore, the compound of the general formula (1) of the present invention can preferably be one of the following specific structural compounds:

[0048]

[0049]

[0050]

[0051]

[0052]

[0053]

[0054]

[0055] The present invention also discloses an application of the thermally activated delayed fluorescent material as described above in an organic electroluminescent device, preferably as a light-emitting layer in the organic electroluminescent device, and more preferably as a light-emitting dye and / or sensitizer in the light-emitting layer of the organic electroluminescent device.

[0056] The above-mentioned compounds of the present invention have thermally activated delayed fluorescence properties.

[0057] The present invention also discloses an application of the above compound in an organic electroluminescent device. The above compound of the present invention is suitable for use as a light-emitting layer material in an organic electroluminescent device, and more preferably used as a light-emitting dye and / or sensitizer in the light-emitting layer of the organic electroluminescent device.

[0058] The application fields of the compounds of the present invention are not limited to organic electroluminescent materials, but can also be applied to optical sensors, solar cells, lighting elements, organic thin film transistors, organic field effect transistors, organic thin film solar cells, information tags, electronic artificial skin sheets, sheet-type scanners and other large-area sensors, electronic paper and other technical fields.

[0059] The present invention also provides an organic electroluminescent device, comprising a substrate, a first electrode, a second electrode and one or more organic layers inserted between the first electrode and the second electrode, wherein the organic layer comprises a compound represented by any one of the above general formula (1), formula (2), and formulas (2-1) to (2-6).

[0060] Specifically, one embodiment of the present invention provides an organic electroluminescent device, comprising a substrate, and an anode layer, a plurality of light-emitting functional layers and a cathode layer sequentially formed on the substrate; the light-emitting functional layer comprises a hole injection layer, a hole transport layer, a light-emitting layer and an electron transport layer, the hole injection layer is formed on the anode layer, the hole transport layer is formed on the hole injection layer, the cathode layer is formed on the electron transport layer, and a light-emitting layer is provided between the hole transport layer and the electron transport layer; wherein the light-emitting layer contains a compound of the present invention represented by any one of the above formulas (1), (2), and (2-1) to (2-6).

[0061] The specific reason why the above-mentioned compounds of the present invention have excellent performance as light-emitting layer materials in organic electroluminescent devices is still unclear, but it is speculated that the reasons may be as follows:

[0062] 1. The compound of the present invention is designed with a double B atom structure, which ensures that the material molecule itself has strong rigidity, and while enhancing the molecular stability of the material, greatly improves the fluorescence quantum yield of the material.

[0063] 2. At least one hydrogen atom in the molecular structure of the compound of the present invention is replaced by deuterium, which can further limit the non-radiative transitions such as vibration and rotation of the molecule, and can help to increase the life of the device after being applied to the organic electroluminescent device.

[0064] 3. Compared with devices prepared using compounds of the present invention as luminescent dyes, organic electroluminescent devices using compounds of the present invention have relatively lower voltage and higher efficiency, and their service life is significantly improved. DETAILED DESCRIPTION

[0065] The specific preparation methods of the above-mentioned novel compounds of the present invention are described in detail below using multiple synthesis examples as examples, but the preparation methods of the present invention are not limited to these synthesis examples. The acquisition of the compound is not limited to the synthesis method and raw materials used in the present invention, and those skilled in the art can also select other methods or routes to obtain the novel compounds proposed in the present invention. The compounds not mentioned in the present invention are raw materials obtained from commercial channels, or are prepared by themselves according to known methods using these raw materials.

[0066] The solvents and reagents used in the synthesis examples, such as dichloromethane, petroleum ether, ethanol, tetrahydrofuran, N,N-dimethylacetamide, anhydrous magnesium sulfate, carbazole and other chemical reagents, can be purchased from the domestic chemical product market, such as Sinopharm Group Reagent Company, TCI Company, Shanghai Bid Pharmaceutical Company, Bailingwei Reagent Company, etc. In addition, those skilled in the art can also synthesize by known methods.

[0067] The analysis and detection of the intermediates and compounds in the synthesis examples were performed using an ABSCIEX mass spectrometer (4000QTRAP).

[0068] The synthesis method of the compound of the present invention is briefly described below.

[0069] Synthesis Example

[0070] Representative synthetic routes:

[0071]

[0072] Synthesis Example 1: Synthesis of Material 6

[0073]

[0074] 1,3,5-tribromobenzene (31.7mmol, 10g), 4,4'-(trideuterated methyl) diphenylamine (127.06mmol, 25.83g), potassium carbonate (127.06mmol, 17.65g), Pd2(dba)3 (0.65mmol, 0.6g), S-Phos (1.27mol, 0.52g) were added to a 1L single-mouth bottle, 300ml of toluene was added, and the reaction was carried out at 100 degrees Celsius under N2 protection overnight. The GC test was carried out the next day. The raw material reaction was complete, 200ml of water was added, the liquid was washed, the crude liquid was passed through the column, and it was evaporated under reduced pressure. It was recrystallized three times using toluene + ethanol to obtain 6-1, 19g, and the yield was 87.9%. It was used for standby after drying. The mass spectrometry test result was: 681.45g / mol.

[0075] 6-1 (22.06mmol, 15g) was added to a 1L single-necked flask, and 200ml of tert-butylbenzene solvent was added. The reaction system was placed in an ice-ethanol bath under N2 protection, and nBu-Li (66.18mmol, 24ml) was slowly added dropwise at -20 degrees Celsius. After the addition was complete, it was heated at 50 degrees Celsius for 2h, and then returned to room temperature. The reaction system was placed in an ice-ethanol bath at -20 degrees Celsius, and boron tribromide (110.29mmol, 27.63g) and diisopropylethylamine (176.47mmol, 22.81g) were added to the reaction system successively, and the room temperature was restored. The reaction was carried out overnight under 100 degrees Celsius N2 protection. TLC test was performed the next day. The raw material reaction was complete, and water was added to quench the reaction. The liquid was separated and dried, and concentrated to dryness under reduced pressure. Purification by column chromatography gave 6-2 5.1g, with a yield of 39.4%. The mass spectrometry test result is: 689.48g / mol.

[0076] 6-2 (6.52mmol, 4.5g) was added to a 1L single-mouth flask, and 100ml of tert-butylbenzene solvent was added. The reaction system was placed in an ice-ethanol bath under N2 protection, and nBu-Li (19.6mmol, 7ml) was slowly added dropwise at -20 degrees Celsius. After the addition was complete, it was heated at 50 degrees Celsius for 2h, and then restored to room temperature. The reaction system was placed in an ice-ethanol bath at -20 degrees Celsius, and boron tribromide (32.62mmol, 8.17g) and diisopropylethylamine (52.19mmol, 16.75g) were added to the reaction system successively, and the room temperature was restored. The reaction was reacted overnight under 100 degrees Celsius N2 protection. TLC test was performed the next day. The raw material reaction was complete, water was added to quench the reaction, the liquid was separated and dried, and it was concentrated to dryness under reduced pressure. Purification by column chromatography gave a final product of 60.87g, with a yield of 19.2%. The mass spectrometry test result was: 697.45g / mol.

[0077] Synthesis Example 2: Synthesis of Material 9:

[0078] The synthesis method is the same as that of material 6, except that 4,4'-(trideuterated methyl)diphenylamine is replaced with an equal amount of bis(4-(prop-2-yl-2-deuterated)phenyl)amine, and finally 1.1 g of material 9 is obtained. The mass spectrometry test result is: 853.56 g / mol.

[0079] Synthesis Example 3: Synthesis of Material 57

[0080]

[0081] 3,5-dibromofluorobenzene (78.77mmol, 20g), Cs2CO3 (157.54mmol, 51.33g), 1,8-dichloro-3,6-dimethylcarbazole (118.16mmol, 31.21g) were added to a 1L single-necked flask at room temperature, and 500ml of DMF was added. The reaction was carried out under N2 protection at 70 degrees Celsius for 4h. TLC detection showed that the raw materials reacted completely. The heating was stopped, and the reaction system was added to 300ml of water. A large amount of solid precipitated. The solid was filtered, washed with ethanol, and then recrystallized twice with toluene + ethanol to obtain 57-1, 34.2g, yield: 87.2%, and dried for use. The mass spectrometry test result was: 494.82g / mol.

[0082] 57-1 (60.24mmol, 30.0g), 4,4'-dideuteratediphenylamine (180.71mmol, 30.94g), potassium carbonate (301.18mmol, 41.62g), Pd2(dba)3 (1.20mmol, 1.10g), S-Phos (3.01mmol, 1.24g) were added to a 1L single-mouth bottle, 300ml of toluene was added, and the reaction was carried out at 100 degrees Celsius under N2 protection overnight. TLC test was performed the next day, 57-1 reacted completely, 200ml of water was added, the liquid was washed, the crude liquid was passed through a column, evaporated to dryness under reduced pressure, and recrystallized three times using toluene + ethanol to obtain 57-2, 32g, yield: 78.3%. After drying, it was used for later use. The mass spectrometry test result was: 677.25g / mol.

[0083] 57-2 (44.20mmol, 30g) was added to a 1L single-necked flask, and 200ml of tert-butylbenzene solvent was added. The reaction system was placed in an ice-ethanol bath under N2 protection, and nBu-Li (221.01mmol, 87ml) was slowly added dropwise at -20 degrees Celsius. After the addition was complete, the mixture was heated at 50 degrees Celsius for 2h, and then returned to room temperature. The reaction system was placed in an ice-ethanol bath at -20 degrees Celsius, and boron tribromide (353.62mmol, 88.59g) and diisopropylethylamine (442.03mmol, 57.13g) were added to the reaction system successively, and the room temperature was restored. The reaction was carried out overnight under 100 degrees Celsius N2 protection. TLC test was performed the next day. The raw material reaction was complete, and water was added to quench the reaction. The liquid was separated and dried, and concentrated to dryness under reduced pressure. Purification by column chromatography gave 57 7.2g, with a yield of 25.9%. The mass spectrometry test result is: 625.26g / mol.

[0084] Synthesis Example 4: Synthesis of Material 73:

[0085] The synthesis method is the same as that of material 57, except that 3,6-dimethylcarbazole is replaced with an equal amount of 3,6-di-tert-butylcarbazole and 4,4'-dideuterated diphenylamine is replaced with an equal amount of bis(phenyl-d5)amine, and finally 738.1 g of material is obtained. The mass spectrometry test result is: 723.49 g / mol.

[0086] Synthesis Example 5: Synthesis of Material 122

[0087]

[0088] 3,5-difluoro-4-deuteriobromobenzene (103.09mmol, 20g), K2CO3 (206.19mmol, 28.50g), 2,2'-dichlorodiphenylamine (154.64mmol, 36.82g), Pd2(dba)3 (2.06mmol, 1.89g), S-Phos (5.15mmol, 2.12g) were added to a 1L single-necked flask at room temperature, and 300ml of toluene was added. The reaction was carried out overnight under N2 protection at 100 degrees Celsius. According to TLC detection, the raw materials reacted completely. Stop heating, add the reaction system to 300ml of water, separate the liquid, pass the crude solution through a column, and concentrate to dryness under reduced pressure. The solid was washed with ethanol and recrystallized twice with toluene + ethanol to obtain 122-1, 31.1g, with a yield of 85.9%. Dry and set aside. The mass spectrometry test result is: 348.03g / mol.

[0089] 122-1 (85.9mmol, 30g), carbazole (257.75mmol, 43.10g), cesium carbonate (343.66mmol, 111.97g) were added to a 1L single-mouth bottle, and 300ml of DMF was added. The reaction was carried out at 100 degrees Celsius under N2 protection overnight. TLC test was performed the next day. 122-1 was completely reacted. 200ml of water was added, and the crude product was precipitated. It was filtered and recrystallized three times using toluene + ethanol to obtain 122-2, 43g, with a yield of 77.5%. It was dried and used for later use. The mass spectrometry test result was: 644.19g / mol.

[0090] 122-2 (30.98mmol, 20g) was added to a 1L single-necked flask, and 300ml of tert-butylbenzene solvent was added. The reaction system was placed in an ice-ethanol bath under N2 protection, and nBu-Li (154.89mmol, 70ml) was slowly added dropwise at -20 degrees Celsius. After the addition was complete, the mixture was heated at 50 degrees Celsius for 2h, and then returned to room temperature. The reaction system was placed in an ice-ethanol bath at -20 degrees Celsius, and boron tribromide (247.83mmol, 62.09g) and diisopropylethylamine (309.79mmol, 40.04g) were added to the reaction system successively, and the room temperature was restored. The reaction was allowed to proceed overnight under 100 degrees Celsius N2 protection. TLC test was performed the next day, and the raw material reaction was complete. Water was added to quench the reaction, the liquid was separated and dried, and the mixture was concentrated to dryness under reduced pressure. Column chromatography was used for purification to obtain 122 5.3g, with a yield of 28.8%. The mass spectrometry test result is: 592.24g / mol.

[0091] Synthesis Example 6: Synthesis of Material 31

[0092]

[0093] 3,5-dibromofluorobenzene (78.77mmol, 20g), 3,6-di(trideuteriomethyl)carbazole (118.16mmol, 23.79g), cesium carbonate (157.54mmol, 51.33g), added to a 500ml single-necked flask at room temperature, added DMF 200ml, reacted for 5h under N2 protection at 100 degrees Celsius, TLC detection, the raw material reaction was complete. Stop heating, add the reaction system to 300ml water, filter the crude product, wash the solid with ethanol and recrystallize it twice with toluene + ethanol to obtain 31-1, 26.5g, yield: 77.3%. Dry and set aside. Mass spectrometry test result: 433.12g / mol.

[0094] 31-1 (45.96mmol, 20g), 2,2'-di(trideuteriomethyl)diphenylamine (137.87mmol, 28.03g), K2CO3 (229.78mmol, 31.76g), Pd2(dba)3 (1mmol, 0.84g), S-Phos (2.3mmol, 0.94g) were added to a 1L single-mouth bottle, and 500ml of toluene was added. The reaction was carried out at 110 degrees Celsius under N2 protection overnight. TLC test was performed the next day. 31-1 reacted completely, 500ml of water was added, the liquid was separated, dried, filtered, and evaporated under reduced pressure. The solid was recrystallized three times using toluene + ethanol to obtain 31-2, 27g, with a yield of 84.7%. It was dried and used for standby use. The mass spectrometry test result was: 679.51g / mol.

[0095] 31-2 (36.76mmol, 25g) was added to a 1L single-necked flask, and 300ml of tert-butylbenzene solvent was added. The reaction system was placed in an ice-ethanol bath under N2 protection, and nBu-Li (110.29mmol, 55ml) was slowly added dropwise at -20 degrees Celsius. After the addition was complete, the mixture was heated at 50 degrees Celsius for 2h, and then returned to room temperature. The reaction system was placed in an ice-ethanol bath at -20 degrees Celsius, and boron tribromide (183.82mmol, 46.05g) and diisopropylethylamine (294.12mmol, 38.01g) were added to the reaction system successively, and the room temperature was restored. The reaction was continued overnight under 100 degrees Celsius N2 protection. TLC test was performed the next day. The raw material reaction was complete, and water was added to quench the reaction. The liquid was separated and dried, and concentrated to dryness under reduced pressure. Purification by column chromatography gave 31-3 11.1g, with a yield of 43.9%. The mass spectrometry test result is: 687.41g / mol.

[0096] 31-3 (14.54mmol, 10g) was added to a 500mL single-necked flask, and 150ml of tert-butylbenzene solvent was added. The reaction system was placed in an ice-ethanol bath under N2 protection, and nBu-Li (43.62mmol, 17.5ml) was slowly added dropwise at -20 degrees Celsius. After the addition was complete, it was heated at 50 degrees Celsius for 2h, and then restored to room temperature. The reaction system was placed in an ice-ethanol bath at -20 degrees Celsius, and boron tribromide (72.7mmol, 18.21g) and diisopropylethylamine (116.3mmol, 15g) were added to the reaction system successively, and the room temperature was restored. The reaction was reacted overnight under 100 degrees Celsius N2 protection. TLC test was performed the next day. The raw material reaction was complete, water was added to quench the reaction, the liquid was separated and dried, and it was concentrated to dryness under reduced pressure. Purification by column chromatography gave 31 1.83g, and the yield was 18.1%. The mass spectrometry test result was: 695.48g / mol.

[0097] Synthesis Example 7: Synthesis of Material 99

[0098]

[0099] 3,5-difluorobromobenzene (103.63mmol, 20g), 4,4'-dideuterated diphenylamine (155.45mmol, 26.62g), potassium carbonate (207.26mmol, 28.46g), Pd2(dba)3 (2.07mmol, 1.9g), S-Phos (5.18mmol, 2.13g) were added to a 500ml single-necked flask at room temperature, and 200ml of toluene was added. The reaction was carried out under N2 protection at 100 degrees Celsius for 5h. TLC detection showed that the raw materials reacted completely. The heating was stopped, and the reaction system was added to 300ml of water, separated, and the crude solution was passed through a column. The solution was concentrated to dryness under reduced pressure. The solid was washed with ethanol and then recrystallized twice with toluene + ethanol to obtain 99-1, 17.5g, with a yield of 59.6%. It was dried and used for standby use. The mass spectrometry test result was: 283.12g / mol.

[0100] 99-1 (64.94mmol, 30.0g), Cs2CO3 (211.78mmol, 69g), 3,6-dicyclohexylcarbazole (158.83mmol, 52.65g) were added to a 1L single-mouth bottle, and DMF 500ml was added. The reaction was carried out at 70 degrees Celsius under N2 protection overnight. TLC test was performed the next day. 99-1 reacted completely. 500ml of water was added. A large amount of solid was precipitated and filtered. The solid was recrystallized three times using toluene + ethanol to obtain 99-2, 36g, with a yield of 74.8%. After drying, it was used for standby. The mass spectrometry test result was: 907.55g / mol.

[0101] 99-2 (33.03mmol, 30g) was added to a 1L single-necked flask, and 500ml of tert-butylbenzene solvent was added. The reaction system was placed in an ice-ethanol bath under N2 protection, and nBu-Li (99.08mmol, 45ml) was slowly added dropwise at -20 degrees Celsius. After the addition was complete, it was heated at 50 degrees Celsius for 2h, and then returned to room temperature. The reaction system was placed in an ice-ethanol bath at -20 degrees Celsius, and boron tribromide (165.14mmol, 41.37g) and diisopropylethylamine (264.22mmol, 34.15g) were added to the reaction system successively, and the room temperature was restored. The reaction was carried out overnight under 100 degrees Celsius N2 protection. TLC test was performed the next day. The raw material reaction was complete, and water was added to quench the reaction. The liquid was separated and dried, and concentrated to dryness under reduced pressure. Purification by column chromatography gave 99-3 11.9g, with a yield of 39.3%. The mass spectrometry test result is: 915.56g / mol.

[0102] 99-3 (10.92mmol, 10g) was added to a 500mL single-necked flask, and 250ml of tert-butylbenzene solvent was added. The reaction system was placed in an ice-ethanol bath under N2 protection, and nBu-Li (32.75mmol, 22.5ml) was slowly added dropwise at -20 degrees Celsius. After the addition was complete, it was heated at 50 degrees Celsius for 2h, and then returned to room temperature. The reaction system was placed in an ice-ethanol bath at -20 degrees Celsius, and boron tribromide (54.58mmol, 13.67g) and diisopropylethylamine (87.32mmol, 11.28g) were added to the reaction system successively, and the room temperature was restored. The reaction was carried out overnight under 100 degrees Celsius N2 protection. TLC test was performed the next day. The raw material reaction was complete, and water was added to quench the reaction. The liquid was separated and dried, and concentrated to dryness under reduced pressure. Purification by column chromatography gave 99 1.49g, with a yield of 14.8%. The mass spectrometry test result is: 923.49 g / mol.

[0103] Synthesis Example 8: Synthesis of Material 172

[0104]

[0105] 1,3,5-tribromobenzene (63.53mmol, 20g), 3,6-di(trideuteriomethyl)carbazole (254.13mmol, 51.16g), potassium carbonate (317.66mmol, 43.90g), Pd2(dba)3 (1.27mmol, 1.16g), S-Phos (3.18mmol, 1.30g) were added to a 500ml single-necked flask at room temperature, and 200ml of toluene was added. The reaction was carried out under N2 protection at 100 degrees Celsius for 5h. After TLC detection, the raw materials reacted completely. The heating was stopped, and the reaction system was added to 300ml of water, separated, and the crude solution was passed through a column. The solution was concentrated to dryness under reduced pressure. The solid was washed with ethanol and then recrystallized twice with toluene + ethanol to obtain 172-1, 23.7g, with a yield of 55.2%. The product was dried and used for later use. The mass spectrometry test result was: 675.44g / mol.

[0106] 172-1 (29.59mmol, 20g) was added to a 1L single-necked flask, and 300ml of tert-butylbenzene solvent was added. The reaction system was placed in an ice-ethanol bath under N2 protection, and nBu-Li (147.94mmol, 60ml) was slowly added dropwise at -20 degrees Celsius. After the addition was complete, the mixture was heated at 50 degrees Celsius for 2h, and then returned to room temperature. The reaction system was placed in an ice-ethanol bath at -20 degrees Celsius, and boron tribromide (236.70mmol, 59.30g) and diisopropylethylamine (295.87mmol, 38.24g) were added to the reaction system successively, and the room temperature was restored. The reaction was allowed to proceed overnight under 100 degrees Celsius N2 protection. TLC test was performed the next day, and the raw material reaction was complete. Water was added to quench the reaction, the liquid was separated and dried, and the mixture was concentrated to dryness under reduced pressure. Column chromatography was used for purification to obtain 3.31g of 172, with a yield of 16.2%. The mass spectrometry test result is: 691.40g / mol.

[0107] Synthesis Example 9: Synthesis of Material 159

[0108]

[0109] 1,3,5-tribromobenzene (63.53mmol, 20g), octa-deuterated carbazole (317.66mmol, 55.67g), potassium carbonate (317.66mmol, 43.90g), Pd2(dba)3 (1.27mmol, 1.16g), S-Phos (3.18mmol, 1.30g) were added to a 500ml single-necked flask at room temperature, and 200ml of toluene was added. The reaction was carried out under N2 protection at 100 degrees Celsius for 5h. TLC detection showed that the raw materials reacted completely. The heating was stopped, and the reaction system was added to 300ml of water, separated, and the crude solution was passed through a column. The solution was concentrated to dryness under reduced pressure. The solid was washed with ethanol and then recrystallized twice with toluene + ethanol to obtain 159-1, 28.6g, with a yield of 75.3%. It was dried and used for later use. The mass spectrometry test result was: 597.42g / mol.

[0110] 159-1 (50.18mmol, 30g) was added to a 1L single-necked flask, and 300ml of tert-butylbenzene solvent was added. The reaction system was placed in an ice-ethanol bath under N2 protection, and nBu-Li (250.90mmol, 90ml) was slowly added dropwise at -20 degrees Celsius. After the addition was complete, the mixture was heated at 50 degrees Celsius for 2h, and then returned to room temperature. The reaction system was placed in an ice-ethanol bath at -20 degrees Celsius, and boron tribromide (401.44mmol, 100.57g) and diisopropylethylamine (501.80mmol, 64.86g) were added to the reaction system successively, and the room temperature was restored. The reaction was allowed to proceed overnight under 100 degrees Celsius N2 protection. TLC test was performed the next day, and the raw material reaction was complete. Water was added to quench the reaction, the liquid was separated and dried, and the mixture was concentrated to dryness under reduced pressure. Purification by column chromatography gave 159 5.96g, with a yield of 19.5%. The mass spectrometry test result is: 609.40g / mol.

[0111] Synthesis Example 10: Synthesis of Material 170:

[0112] The synthesis method is the same as that of material 159, except that octa-deuterated carbazole is replaced with an equal amount of 3,6-bis(propan-2-yl-2-deuterium)-9H-carbazole, and finally 6.13 g of material 170 is obtained. The mass spectrometry test result is: 847.49 g / mol.

[0113] Synthesis Example 11: Synthesis of Material 181:

[0114] The synthesis method is the same as that of material 159, except that octa-deuterated carbazole is replaced with an equal amount of deuterated 3,6-di-tert-butyl-9H-carbazole, and finally 6.13 g of material 181 is obtained. The mass spectrometry test result is: 979.94 g / mol.

[0115] Device Embodiment

[0116] Implementation

[0117] OLED includes a first electrode, a second electrode, and an organic material layer between the electrodes. The organic material can be divided into multiple regions. For example, the organic material layer can include a hole transport region, a light emitting layer, and an electron transport region.

[0118] In a specific embodiment, a substrate may be used below the first electrode or above the second electrode. The substrate is a glass or polymer material with excellent mechanical strength, thermal stability, water resistance, and transparency. In addition, a thin film transistor (TFT) may also be provided on the substrate used as a display.

[0119] The first electrode can be formed by sputtering or depositing the material used as the first electrode on the substrate. When the first electrode is used as an anode, an oxide transparent conductive material such as indium tin oxide (ITO), indium zinc oxide (IZO), tin dioxide (SnO2), zinc oxide (ZnO) and any combination thereof can be used. When the first electrode is used as a cathode, a metal or alloy such as magnesium (Mg), silver (Ag), aluminum (Al), aluminum-lithium (Al-Li), calcium (Ca), magnesium-indium (Mg-In), magnesium-silver (Mg-Ag) and any combination thereof can be used.

[0120] The organic material layer can be formed on the electrode by vacuum thermal evaporation, spin coating, printing, etc. The compound used as the organic material layer can be organic small molecules, organic macromolecules and polymers, and combinations thereof.

[0121] The hole transport region is located between the anode and the light-emitting layer. The hole transport region can be a hole transport layer (HTL) of a single-layer structure, including a single-layer hole transport layer containing only one compound and a single-layer hole transport layer containing multiple compounds. The hole transport region can also be a multi-layer structure including at least one layer of a hole injection layer (HIL), a hole transport layer (HTL), and an electron blocking layer (EBL).

[0122] The material of the hole transport region can be selected from, but not limited to, phthalocyanine derivatives such as CuPc, conductive polymers or polymers containing conductive dopants such as polyphenylene ethylene, polyaniline / dodecylbenzenesulfonic acid (Pani / DBSA), poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonate) (PEDOT / PSS), polyaniline / camphorsulfonic acid (Pani / CSA), polyaniline / poly(4-styrenesulfonate) (Pani / PSS), aromatic amine derivatives such as the compounds shown in HT-1 to HT-34 below; or any combination thereof.

[0123]

[0124]

[0125]

[0126] The hole injection layer is located between the anode and the hole transport layer. The hole injection layer can be a single compound material or a combination of multiple compounds. For example, the hole injection layer can use one or more compounds of HT-1 to HT-34, or one or more compounds of HI-1 to HI-3 described below; or one or more compounds of HT-1 to HT-34 can be doped with one or more compounds of HI-1 to HI-3 described below.

[0127]

[0128] The light-emitting layer includes a light-emitting dye (i.e., dopant) that can emit light of different wavelength spectra, and may also include a host material (Host). The light-emitting layer may be a monochrome light-emitting layer that emits a single color such as red, green, and blue. A plurality of monochrome light-emitting layers of different colors may be arranged in a plane according to a pixel pattern, or may be stacked together to form a color light-emitting layer. When light-emitting layers of different colors are stacked together, they may be separated from each other or may be connected to each other. The light-emitting layer may also be a single color light-emitting layer that can simultaneously emit different colors such as red, green, and blue.

[0129] In one aspect of the present invention, the light-emitting layer adopts fluorescent electroluminescence technology. The fluorescent host material of the light-emitting layer can be selected from, but not limited to, one or more combinations of FH-1 to FH-17 listed below.

[0130]

[0131]

[0132] In one aspect of the present invention, the light-emitting layer adopts the electroluminescence technology of thermally activated sensitized fluorescence. In addition to the light-emitting material of the present invention, the light-emitting layer also includes a combination of one or more of a wide-bandgap host material and a thermally activated delayed fluorescent material.

[0133] The main material can be selected from, but not limited to, the following H-1 to H-43:

[0134]

[0135]

[0136]

[0137]

[0138] The thermally activated delayed fluorescent material may be selected from, but not limited to, T-1 to T-92 listed below:

[0139]

[0140]

[0141]

[0142]

[0143]

[0144] The OLED organic material layer may further include an electron transport region between the light emitting layer and the cathode. The electron transport region may be a single-layer electron transport layer (ETL), including a single-layer electron transport layer containing only one compound and a single-layer electron transport layer containing multiple compounds. The electron transport region may also be a multilayer structure including at least one layer of an electron injection layer (EIL), an electron transport layer (ETL), and a hole blocking layer (HBL).

[0145] In one aspect of the present invention, the electron transport layer material can be selected from, but not limited to, one or more combinations of ET-1 to ET-57 listed below.

[0146]

[0147]

[0148]

[0149] The device may further include an electron injection layer located between the electron transport layer and the cathode. Materials for the electron injection layer include, but are not limited to, one or more combinations of the following.

[0150] LiQ, LiF, NaCl, CsF, Li2O, Cs2CO3, BaO, Na, Li, Ca.

[0151] Device Example 1

[0152] In the fluorescent device embodiment 1, the device structure is as follows:

[0153] ITO (150nm) / HI-2 (10nm) / HT-4 (40nm) / FH-4:6 (30nm, 3% wt) / ET-53 (25nm) / LiF (0.5nm) / Al (150nm). The organic electroluminescent device preparation process is as follows: a glass plate coated with a transparent conductive layer of ITO (thickness 150nm) is ultrasonically treated in a commercial cleaning agent, rinsed in deionized water, ultrasonically degreased in a mixed solvent of acetone: ethanol, baked in a clean environment until the water is completely removed, cleaned with ultraviolet light and ozone, and bombarded with a low-energy cation beam;

[0154] Place the glass substrate with the anode in a vacuum chamber and evacuate the chamber to a vacuum of less than 1×10 -5 Pa, HI-2 and HT-4 were vacuum evaporated on the above anode layer as hole injection layer and hole transport layer, respectively, with an evaporation rate of 0.1 nm / s and an evaporation film thickness of 10 nm and 40 nm, respectively;

[0155] "FH-4:6 (30nm, 3%wt)" is vacuum evaporated on the hole transport layer as the light-emitting layer of the organic electroluminescent device. The evaporation rate is 0.1nm / s and the total film thickness of the evaporation is 30nm; wherein "3%wt" refers to the doping ratio of the dye, that is, the weight ratio of the main material to the compound 6 of the present invention is 97:3.

[0156] ET-53 was vacuum-deposited on the light-emitting layer as the electron transport layer of the organic electroluminescent device, with a deposition rate of 0.1 nm / s and a total deposition film thickness of 25 nm;

[0157] 0.5 nm of LiF as an electron injection layer and 150 nm of Al as a cathode were vacuum-deposited on the electron transport layer.

[0158] The manufacturing process of device examples 2-10 and comparative example 1 is the same as that of device example 1, except that the compound 6 of the present invention as the luminescent dye is replaced by the compound of the present invention 9, 10, 22, 34, 43, 73, 106, 170, 181 and prior art Compound R-1 .

[0159] The prior art compound used in Comparative Example 1:

[0160]

[0161] In the thermally activated sensitized fluorescence device embodiment 11, the device structure is as follows:

[0162] ITO (150nm) / HI-2 (10nm) / HT-4 (40nm) / H-41:T-89:6 (100:30:3, w / w / w) (30nm) / ET-53 (25nm) / LiF (0.5nm) / Al (150nm). The organic electroluminescent device preparation process is as follows: a glass plate coated with a transparent conductive layer of ITO (thickness 150nm) is ultrasonically treated in a commercial cleaning agent, rinsed in deionized water, ultrasonically degreased in a mixed solvent of acetone: ethanol, baked in a clean environment until the water is completely removed, cleaned with ultraviolet light and ozone, and bombarded with a low-energy cation beam;

[0163] Place the glass substrate with the anode in a vacuum chamber and evacuate the chamber to a vacuum of less than 1×10 -5 Pa, HI-2 and HT-4 were vacuum evaporated on the above anode layer as hole injection layer and hole transport layer, respectively, with an evaporation rate of 0.1 nm / s and an evaporation film thickness of 10 nm and 40 nm, respectively;

[0164] "H-41:T-89:6 (100:30:3, w / w / w) (30 nm)" was vacuum-deposited on the hole transport layer as the light-emitting layer of the organic electroluminescent device. The total deposition rate was 0.1 nm / s and the total deposition film thickness was 30 nm. The weight ratio of H-41:T-89:Compound 6 was set to 100:30:3.

[0165] ET-53 was vacuum-deposited on the light-emitting layer as the electron transport layer of the organic electroluminescent device, with a deposition rate of 0.1 nm / s and a total deposition film thickness of 25 nm;

[0166] 0.5 nm of LiF as an electron injection layer and 150 nm of Al as a cathode were vacuum-deposited on the electron transport layer.

[0167] The manufacturing process of device examples 12-17 and comparative example 2 is the same as that of device example 11, except that the compound 6 of the present invention as the luminescent dye is replaced by the compound of the present invention 10, 47, 77, 155, 170, 181 and compounds of the prior art R-1 .

[0168] The organic electroluminescent device prepared by the above process was subjected to the following performance tests:

[0169] At the same brightness, a digital source meter and a brightness meter were used to measure the driving voltage and current efficiency of the organic electroluminescent devices prepared in Examples 1-10 and Comparative Example 1, as well as the device life. Specifically, the voltage was increased at a rate of 0.1 V per second, and the brightness of the organic electroluminescent device was measured when it reached 1000 cd / m 2 The voltage at which the light is on is the driving voltage, and the current density at this time is measured at the same time; the ratio of brightness to current density is the current efficiency; the life test of LT95 is as follows: use a brightness meter at 1000cd / m 2 At the same brightness, the current is kept constant and the brightness of the organic electroluminescent device is measured to drop to 950cd / m 2 time.

[0170] Among the fluorescent devices, the specific performance data of the organic electroluminescent devices prepared in the above-mentioned Examples 1-10 and Comparative Example 1 of the present invention are detailed in Table 1 below, wherein the lifetime value of Comparative Example 1 is taken as 1.0, and the lifetime values ​​in other examples are ratios thereto.

[0171] Table 1

[0172]

[0173] The organic electroluminescent devices prepared by the above process were subjected to the following performance tests: Under the same brightness, the turn-on voltage and maximum brightness of the organic electroluminescent devices prepared in device examples 11 to 17 and device comparative example 2 were measured using a digital source meter and a brightness meter, and the maximum external quantum efficiency was calculated. Specifically, the voltage was increased at a rate of 0.1 V per second, and the brightness of the organic electroluminescent device was measured when it reached 1000.00 cd / m 2 The voltage at which the light is turned on is the turn-on voltage. The current density at this time is measured and the maximum external quantum efficiency is calculated based on the spectrum and other data. The life test of LT95 is as follows: Use a brightness meter at 1000cd / m 2 At the same brightness, the current is kept constant and the brightness of the organic electroluminescent device is measured to drop to 950cd / m 2 time.

[0174] The specific performance data of the organic electroluminescent devices prepared in Examples 11-17 of the present invention and Comparative Example 2 are shown in Table 2 below, wherein the lifetime value of Comparative Example 2 is taken as 1.0, and the lifetime values ​​in other examples are ratios thereto.

[0175] Table 2

[0176]

[0177] The above results show that the novel double B-type organic compound of the present invention is used in organic electroluminescent devices. Since the compound has a rigid planar conjugated structure, it has a high fluorescence quantum yield and stability and is a luminescent material with good performance. At the same time, the deuteration of some atoms in the compound also restricts the vibration and rotation of the molecule to a certain extent, which has obvious advantages in improving the life of the device using the compound.

[0178] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

[0179] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A compound of the general formula, as shown in the following formula (1): In formula (1), the dotted line indicates that they can be connected to form a ring or not; R a , R b , R c , R d Each independently represents a single substituent to the maximum permissible substituent, and each independently is selected from one of hydrogen, substituted or unsubstituted C1-C12 chain alkyl, substituted or unsubstituted C3-C12 cycloalkyl, and substituted or unsubstituted C6-C30 arylamino; R e is hydrogen; And the R a , R b , R c , R d and R e At least one of them is a deuterated C1-C12 chain alkyl or a deuterated C3-C12 cycloalkyl; Ar 1 and Ar 2 Each is independently selected from substituted or unsubstituted C6-C30 aryl; Ar 1 With Ring 1 and / or R a Connected into a ring or not connected into a ring; Ar 2 With Ring 3 and / or R d Connected into a ring or not connected into a ring; The R a , R b , R c , R d and R e At least one of the hydrogen atoms is deuterated; When the above-mentioned substituted or unsubstituted groups have substituents, the substituents are selected from one or more of deuterium, halogen, C1-C12 chain alkyl, C3-C12 cycloalkyl, deuterated C1-C12 chain alkyl, deuterated C3-C12 cycloalkyl, C6-C30 arylamino, and C3-C30 heteroarylamino.

2. According to any one of the compounds described in claim 1, in formula (1), Ar 1 and Ar 2 Each is independently selected from a substituted C6-C30 aryl group having at least one substituent group, or a substituted C3-C30 heteroaryl group having at least one substituent group, wherein the substituent group is selected from deuterium, a deuterated C1-C12 chain alkyl group or a deuterated C3-C12 cycloalkyl group.

3. A compound according to any one of claims 1-2, as shown in the following formula (2): In formula (2), the dotted line indicates that they can be connected to form a ring or not; R a , R b , R c , R d and R e The definition of is the same as that in formula (1); R f and R g Each independently represents a single substituent to the maximum permissible substituent, and each independently is selected from one of hydrogen, C1-C12 chain alkyl, C3-C12 cycloalkyl, and C6-C30 arylamino; Furthermore, at least one hydrogen atom in the compound structure represented by formula (2) is deuterated.

4. The compound according to claim 3, as shown in the following formula (2-1) to formula (2-6): In formula (2-1) to formula (2-6), R a , R b , R c , R d , R e , R f and R g The definition of is the same as that in formula (2), and at least one hydrogen in the compound structures represented by formula (2-1) to formula (2-6) is deuterated.

5. The compound according to claim 2 or 3, wherein in the formula (2) or the formula (2-1) to the formula (2-6), R a , R b , R c , R d , R e and R f and R g At least one of them is deuterium.

6. The compound according to claim 2, as shown in the following formula (2-4) to formula (2-6): In the above formulas (2-4) to (2-6), R a , R b , R c , R d , R e and R f and R g At least one of them is a deuterated C1-C12 chain alkyl group or a deuterated C3-C12 cycloalkyl group.

7. A compound selected from the following structural compounds:

8. Use of the compound according to any one of claims 1 to 7 as a light-emitting layer material in an organic electroluminescent device, specifically as a light-emitting dye and / or a sensitizer.

9. An organic electroluminescent device, comprising an anode layer, a plurality of light-emitting functional layers and a cathode layer; the plurality of light-emitting functional layers comprise at least one of a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer and an electron transport layer formed in sequence, the hole injection layer is formed on the anode layer, and the cathode layer is formed on the electron transport layer; wherein, The light-emitting layer contains the organic compound according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Organic molecules, in particular for use in optoelectronic devices

    CA3017010A1

  • Novel compound and organic light emitting device using same

    CN110225917A

  • Novel compound and applications thereof, and organic electroluminescent device using compound

    CN110407858A